Child Soldiers: Tropes of Innocence and Terror - David Rosen (Antropologia)
The image of child soldiers has dramatically shifted over time. In the past, child soldiers were often celebrated as symbols of virtue and patriotism, as seen with figures like Andrew Jackson. However, modern views portray them as tragic victims of war, embodying a stark contrast between childhood innocence and the brutal realities of conflict. This change reflects broader social shifts in the understanding of childhood, family authority, and state power. The challenge today lies in reconciling the idealized notions of childhood with the harsh empirical realities faced by child soldiers in contemporary warfare.